A survey of protein interactions and posttranslational modifications that influence the polyglutamine diseases - Johnson, Sean L.; Tsou, Wei-Ling; Prifti, Matthew V.; Harris, Autumn L.; Todi, Sokol V. (Frontiers in Molecular Neuroscience, 2022)
The presence and aggregation of misfolded proteins has deleterious effects in the nervous system. Among the various diseases caused by misfolded proteins is the family of the polyglutamine (polyQ) disorders. This family comprises nine members, all stemming from the same mutation—the abnormal elongation of a polyQ repeat in nine different proteins — which causes protein misfolding and aggregation, cellular dysfunction and disease. While it is the same type of mutation that causes them, each disease is distinct: it is influenced by regions and domains that surround the polyQ repeat; by proteins with which they interact; and by posttranslational modifications they receive. Here, we overview the role of non-polyQ-regions that control the pathogenicity of the expanded polyQ repeat. We begin by introducing each polyglutamine disease, the genes affected, and the symptoms experienced by patients. Subsequently, we provide a survey of protein-protein interactions and posttranslational modifications that regulate polyQ toxicity. We conclude by discussing shared processes and pathways that bring some of the polyQ diseases together and may serve as common therapeutic entry points for this family of incurable disorders.